Simulation of a coil cooling system for an innovative compound solar concentrator plant by FEM approach. (November 2020) - Carlini, Maurizio; Rotondo, Mirko; Selli, Sara; Mennuni, Andrea
Abstract: Nowadays the environmental policies have been changing to reduce the emission of pollutants, promoting as a consequence the exploitation of renewable energy sources. In those terms, the solar energy has to be considered one of the most suitable solutions as an energy source. However, many efforts have been made to improve the efficiency of photovoltaic energy conversion systems. The work presents a multi-physical analysis of a Compound Parabolic Concentrator (CPC) provided with a coil cooling system fed by water. The transient scenarios are solved by implementing both heat transfer and non-isothermal pipe flow phenomena. The simulation software COMSOL Multiphysics is used to solve the FEM scenarios, investigating the temperature field of the solar cells and the heating of water inside the coils. A CPC-powered photovoltaic plant, composed by a series of 18 cooled CPCs, is considered to define the thermal response of the whole system while cooling water flows inside the coils. A comparison with a non-cooled CPC-powered photovoltaic plant is then conducted. Results quantify how the presence of a cooling system decreases the temperature on the solar cells, improving in the meanwhile the efficiency of the whole system, directly related to the conversion of sun radiation into electrical energy by photovoltaic effect. The efficiency of the whole system for the first CPC without and with coils is about 22.4% and 27.2%, respectively. At the 18th CPC the efficiency of the whole system of the cooled CPC decreases up to 24% due to the decreasing efficiency of the cooling coils. Furthermore, the outlet water temperature from coils increases with the number of CPCs and it reaches a peak at the 18th CPC of 48 °C. The increasing water temperature offers the possibility of its recovery for different applications which require such thermal gap.